2019
DOI: 10.1177/1744987119835873
|View full text |Cite
|
Sign up to set email alerts
|

Participant perceptions of virtual simulation to develop non-technical skills in health professionals

Abstract: Background Research has identified that virtual simulations may be effective in developing non-technical skills including communication, teamwork and decision making. However, little is known about how participants perceive learning non-technical skills via engagement in virtual simulation. Aims The aim of this research was to investigate participant perceptions and the learning experiences when engaging in virtual simulations focused on developing non-technical skills. Method A descriptive exploratory approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Our findings also corroborate those of a qualitative studies [ 11 , 68 ] and those reported in an integrative review ( n = 38 articles) [ 18 ] that explored how VP simulation influenced the non-technical skills (such as communication) of undergraduate nursing students [ 11 ] and undergraduate health professional education [ 18 ]. The findings suggest that students acknowledged the importance of communication and listening to their patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings also corroborate those of a qualitative studies [ 11 , 68 ] and those reported in an integrative review ( n = 38 articles) [ 18 ] that explored how VP simulation influenced the non-technical skills (such as communication) of undergraduate nursing students [ 11 ] and undergraduate health professional education [ 18 ]. The findings suggest that students acknowledged the importance of communication and listening to their patients.…”
Section: Discussionsupporting
confidence: 89%
“…The VP “opened their eyes” to the impacts either effective or poor communication had on healthcare [ 18 ]. VP simulation exerted a positive influence on students, by reinforcing or teaching new communication skills, providing opportunities for practicing those skills and for building their confidence in applying them, developing specific verbal and nonverbal communication skills [ 11 ] and developing awareness of non-technical skills including but not limited to communication [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Described within this manuscript is the role that academic institutions are called to fulfill as key contributors to the state of healthcare and the opportunity to organize intentional scalable models of simulation-enhanced IPE (SIM-IPE) focusing on non-technical skill (NTS) development using an online delivery modality. NTS can be comprised of competencies related to situational awareness, leadership, communication, decision-making, and teamwork activities (Coggin et al, 2017;Peddle, 2019). Flin et al (2013) describes NTS as "cognitive, social and personal resource skills that complement workers' technical skills and contribute to safe and efficient task performance" (p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of this four week simulation placement (120 hours block) was undertaken as simulation based education (SBE). Simulation based education has become integral to nursing education (INACSL, 2017), particularly as studies have shown that students can develop confidence, critical thinking, clinical reasoning, technical and non-technical skills (George and Quatrara, 2018;Morrell-Scott, 2018;Peddle, 2019b;Raman et al, 2019;Teles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, within the UK student nurses have to undertake considerably more practice placement hours increasing pressure to find high quality placements compared to other countries, please see Table 1: This modality has become more widely adopted by nurse educators over the last few years, in particular due to a massive surge of interest and usage due to COVID 19. Indeed, the accessibility of web based learning is creating a paradigm shift to online pedagogy (Peddle, 2019a;Lu, 2020). Therefore, the development team aimed to use appropriate and innovative technology with innovative, immersive e-simulation.…”
Section: Introductionmentioning
confidence: 99%